Pathways to teacher performance: a multivariate analysis of transformational leadership, empowerment, trust, and achievement motivation - Juli Hartini; Sri Setyaningsih; Suhendra (Jurnal Konseling dan Pendidikan, 2025)
Teacher performance is a key determinant of educational quality and school effectiveness and is shaped by the interaction of organizational and psychological factors. This study examines a multivariate model of teacher performance by analyzing the direct and indirect effects of transformational leadership, empowerment, and trust through achievement motivation among junior high school teachers in Bekasi City. A quantitative survey design was employed involving 177 teachers selected through multistage proportional random sampling from 19 schools across six districts. Data were collected using validated scales adapted from established studies and measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess direct and indirect relationships, complemented by the SITOREM method for indicator prioritization. The results indicate that transformational leadership (β = 0.351), empowerment (β = 0.195), trust (β = 0.271), and achievement motivation (β = 0.189) have significant positive direct effects on teacher performance, while transformational leadership and empowerment also exert indirect effects through trust (β = 0.091; β = 0.055) and achievement motivation (β = 0.075; β = 0.033). The structural model explains a substantial proportion of variance in teacher performance (R²), indicating strong model robustness. SITOREM analysis identifies work quantity, job achievement, and achievement stimulation as priority indicators for improvement, whereas work quality and teamwork should be maintained. This study contributes theoretically by validating a multivariate teacher performance model and practically by providing a data-driven framework to help school leaders and policymakers strategically enhance teacher performance in secondary education contexts.